PERANCANGAN SIGN SYSTEM YANG TERINTEGRASI WEBSITE SEBAGAI MEDIA INFORMASI - Ramzy Adzhar; Wirania Swasty (LPPM Institut Bisnis dan Teknologi Indonesia, 2019)
Setu Babakan Betawi Culture Village is one of the tourist attractions in the capital area. Locating in the middle of the capital, this tourist attraction can be used as a place for relaxation. Problems begin as it is currently happening in wayfinding and a sign system that does not get the attention of the management, which is less informative and inappropriate placement. The thing to concern is by creating a website that provides various information and directions for tourist objects and existing facilities. Data collection is done through interviews, questionnaires, and observations to find out more about the object of research. The process of analysis is done by comparing similar objects. This study produces a sign system that integrates a website using the QR Code as an information media in the Setu Babakan Betawi Village area. It is expected to help informing the location and facilities there for visitors.